2020
DOI: 10.1177/1758573220909981
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and clinical outcomes of second generation Trabecular Metal™ glenoid components in total shoulder arthroplasty

Abstract: Background Total shoulder arthroplasty with second generation porous tantalum glenoid implants (Trabecular Metal™) has shown good short-term outcomes, but mid-term outcomes are unknown. This study describes the clinical, radiographic, and patient-rated mid-term outcomes of total shoulder arthroplasty utilizing cemented Trabecular Metal™ glenoid components. Methods Patients who underwent anatomic total shoulder arthroplasty with cemented Trabecular Metal™ glenoid components for primary osteoarthritis were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 9 , 19 Our study found a lower rate of debris (6.5%) and severity (Grade 1) when compared to the literature, and might be attributed to our shorter follow-up period. Chen et al 10 identified debris in 24% of patients in their series at a mean 80 months with four patients categorized as Grade 1 and one patient as Grade 2. A subsequent retrospective study by the same author explored differences in metal debris between cemented and uncemented second-generation TM glenoids.…”
Section: Discussionmentioning
confidence: 97%
“… 9 , 19 Our study found a lower rate of debris (6.5%) and severity (Grade 1) when compared to the literature, and might be attributed to our shorter follow-up period. Chen et al 10 identified debris in 24% of patients in their series at a mean 80 months with four patients categorized as Grade 1 and one patient as Grade 2. A subsequent retrospective study by the same author explored differences in metal debris between cemented and uncemented second-generation TM glenoids.…”
Section: Discussionmentioning
confidence: 97%